Use of coconut water (Cocos nucifera) as intravenous electrolytic therapy in dehydrated canines - Mendoza Q., Yamili (2018)
The objective of this study was to evaluate the use of coconut water (AC) applied intravenously in dogs. In a first phase the sterility and isotonicity of the CA was evaluated. In a second phase, the hematological changes produced 24 hours after the application of CA by intraperitoneal route in rats were evaluated. In a third phase the application of AC applied intravenously was evaluated in dogs with and without physical activity (n=20, per group), where the hematological values, pH and chlorine and sodium levels were determined before and after its application, as well as the heart rate, respiratory rate and temperature at the beginning, at 15, 30, 45, 60 minutes after the start of the application and 30 minutes after the application of the AC. The results showed that AC is sterile and isotonic, did not produce significant alterations in the hematological values of rats or in dogs without physical activity. However, dogs with physical activity showed a reduction in hematocrit at 30 minutes after application and a slight reduction in sodium levels.